(untitled) (World of finance, 2019)
Introduction. In the current conditions of the integration movement of Ukraine to the European Union and the reform of the institutions of state power, the issue of studying foreign experience of the system of taxation of individuals’ incomes is actualized. The application of effective practices of other states will contribute to increasing the fiscal role of the personal income tax in Ukraine, reducing social inequality and increasing the welfare of the population. Purpose. The purpose of the article is to find out the features, trends and problems of the functioning of the personal income tax in foreign countries. Results. The article deals with the foreign experience of functioning of the system of personal income taxation. The role and role of PIT in the EU and OECD countries is shown. The proportional and progressive approach to taxation of this tax is considered, their key advantages and disadvantages are determined. An analogy has been made between the European states, the OECD member states and Ukraine. The objective necessity of establishing a non-taxable minimum or partial exemption of citizens’ incomes from taxes in the context of support of low-income categories of the population and ensuring social justice is substantiated. Conclusions. It is concluded that in developed countries, the progressive system of taxation of the PIT along with the minimum non-taxable minimum is an effective tool for generating budget revenues and solving social inequalities in society. Instead, third-world states can not use this mechanism in a qualitative way due to significant tax compliance problems. They apply a proportional taxation system for PIT that minimizes tax evasion and international competitiveness.